Star-forming Main Sequence of Giant Low Surface Brightness Galaxies - Wei Du; Cheng Cheng; Pengliang Du; Lin Du; Hong Wu (The Astrophysical Journal, 2023)
Giant low surface brightness galaxies (GLSBGs) are fundamentally distinct from normal galaxies and other types of LSBGs in terms of star formation and evolution. In this work, we collected 27 local GLSBGs from the literature. They have high stellar masses ( M _* > 10 ^10 M _⊙ ) and low far-ultraviolet-based star formation rates (SFRs). With specific star formation rates (sSFRs) lower than the characteristic value of local star-forming galaxies (SFGs) of M _* = 10 ^10 M _⊙ (sSFR < 0.1 Gyr ^−1 ), GLSBGs deviate from the star formation main sequence (MS) defined for local SFGs respectively by Elbaz et al. (E07) and Saintonge et al. (S16) at the high- M _* regime. They are H i -rich systems with H i gas mass fractions ( f _H I ) higher than the S16 MS galaxies, but have little molecular gas (H _2 ), implying a quite low efficiency of H i -to-H _2 transition due to low H i surface densities (Σ H i ) that are far lower than the minimum Σ H i of 6–8 M _⊙ pc ^−2 required for shielding the formed H _2 from photodissociation. For GLSBGs, the inner, bulge-dominated parts with lower SFRs and higher M _* are the main force pulling the entire GLSBG sample off of the MS, while the outer, disk-dominated parts with relatively higher SFRs and lower M _* reduce the deviation from the MS. For some cases, the outer, disk-dominated parts even tend to follow the MS. In the aspect of near-ultraviolet − r versus g − r colors, the outer, disk-dominated parts are blue and behave similarly to normal SFGs while the inner, bulge-dominated parts are statistically redder, indicating an inside–out star formation mechanism for GLSBGs. They show few signs of external interactions in morphology, excluding the recent major merger scenario.